Kinerja Usahatani Petani Padi di Lahan Pertanian Pangan Berkelanjutan (LP2B) Kabupaten Subang - Nugraha, Adi; Heryanto, Mahra Arari (Universitas Galuh, 2024)
LP2B is a program designed to maintain and increase the productivity of agricultural land, particularly for rice, to ensure a sufficient food supply for the Indonesian people. However, the contribution of rice farming to farmers’ income on this land has not received enough attention. This research aims to measure the performance of rice farming in LP2B area in Subang Regency, one of the main rice-producing areas in West Java. Primary data was collected through semi-structured interviews conducted with 364 paddy farmer respondents who cultivate in the LP2B area. Farming performance was calculated using farming economic viability analysis. The results show that in terms of performance, rice farming in the LP2B area of Subang Regency is profitable, with a B/C value of 0.9 for land less than 0.5 hectares, B/C value 1,2 for land between 0.5 and 1 hectare, and B/C value of 1,3 for land above 1 hectare.